2018
DOI: 10.1111/caim.12270
|View full text |Cite
|
Sign up to set email alerts
|

Creative ventures and the personalities that activate them in a post‐disaster setting

Abstract: In the post‐earthquakes setting of Christchurch, New Zealand, the realization of value for the affected community occurred in a variety of ways. Data for this study were gathered from in‐depth interviews (n = 45) with people involved in a range of creative ventures pursued for commercial or social benefit during the five years following the earthquakes in Christchurch, New Zealand in 2010 and 2011. Perhaps unexpectedly, the unstable setting delivered a multitude of opportunities for entrepreneurship and a redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…The results of our research have proven, that it is necessary for the individual to consider uncertain and ambiguous situations as opportunities for professional growth, learning new things, relevant to the scientific results of empirical research on the impact of creativity on activities in critical situations. This study has confirmed that an unstable environment provides many opportunities for entrepreneurship and reduces the level of perceived risk (Cameron et al, 2018). The main study, different from ours, is the scientific research, which proves that the focus on innovations and creativity of staff is an alternative to any other investment and prerogative in human capital management, confirms the correlation between employees' creativity and company's productivity in general, between employees' creativity and their level of well-being (Miao & Cao, 2019).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The results of our research have proven, that it is necessary for the individual to consider uncertain and ambiguous situations as opportunities for professional growth, learning new things, relevant to the scientific results of empirical research on the impact of creativity on activities in critical situations. This study has confirmed that an unstable environment provides many opportunities for entrepreneurship and reduces the level of perceived risk (Cameron et al, 2018). The main study, different from ours, is the scientific research, which proves that the focus on innovations and creativity of staff is an alternative to any other investment and prerogative in human capital management, confirms the correlation between employees' creativity and company's productivity in general, between employees' creativity and their level of well-being (Miao & Cao, 2019).…”
Section: Discussionsupporting
confidence: 70%
“…The researchers have justified positive effect of improvisation on the formation of creativity and tolerance for ambiguity (Felsman et al, 2020), have offered training as a means of developing person's creative potential and overcoming stress under conditions of uncertainty , have emphasized the importance of empathy and emotional intelligence in decision-making in the situations of uncertainty (Vyatkin et al, 2020). There is clear positive correlation between employees' creativity and the level of implementation of innovations under conditions of risk and uncertainty (Zheng & Miller, 2017), between a person's creativity and psychological well-being in the context of global destruction (Orkibi, 2021), between creativity and formation of leadership qualities of the individual (Oosthuizen, 2020), between tolerance for ambiguity and creativity, job satisfaction, welfare of the employees, development of critical thinking, success and efficiency of activities of the organization in volatile environments (O'Connor et al, 2017;Cameron et al, 2018;Miao & Cao, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A creative entrepreneur is an individual who has an entrepreneurial mindset in response to two triggers for the entrepreneurial act: extrinsic, that is, contextual and business driven, and intrinsic, that is, involving internal desire to create something aesthetic and focused on a sense of personal achievement (Henry and De Bruin, 2011). Although there seems to be no clear distinction or consensual understanding regarding the meanings of creative entrepreneurs in the extant literature (Hausmann and Heinze, 2016), creative entrepreneurs can be understood as those enacting novel and useful ideas to add social or commercial value by producing products to meet market demands while simultaneously satisfying their own creative and artistic sensibility (Cameron et al , 2018; Gundolf et al , 2018). More satisfied entrepreneurs work more effectively with their customers and employees, which results in greater success or favorable career outcomes and further moves business forward (Carree and Verheul, 2012; Cooper and Artz, 1995; Gavin and Mason, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For SMSTs suffering an economic downturn, passion could represent a hidden resource able to ignite a variety of entrepreneurial processes with both non-profit and profit orientation (Crick et al, 2020). This could generate value for the community in the case of postdisaster contexts requiring a creative effort in both business and social settings (Cameron et al, 2018). Therefore, the first task for policymakers should be directed toward active monitoring of what is under the surface of local economic and cultural activism, which then could be turned in viable new business ventures.…”
Section: Discussionmentioning
confidence: 99%